2021
DOI: 10.3390/app112210945
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Biochar-Based Geopolymer Materials

Abstract: The aim of this research is to evaluate the possibility to realize alkali-activated materials exploiting biochar, a secondary raw material coming from pyrolysis/gasification processes, for environmental benefits, such as improvement of soil fertility and reduction of CO2 emissions into the atmosphere thanks to the carbon sink process where carbon dioxide is subtracted from the cycle of carbon. For the matrix of the geopolymers, a waste material derived from incinerator bottom ash was used and compared to pure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The study [ 37 ] analysed the effect of NaOH concentration (6–14 M) on the mechanical properties of kaolin geopolymers. Compressive strength results showed that the optimum NaOH concentration is 8 M. Moreover, according to research results [ 3 , 4 , 11 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 37 , 38 , 39 , 40 , 42 , 43 ], the soluble glass to 8 M of NaOH solution ratio should be around 2.5 to give geopolymers high compressive strength [ 37 , 40 ]. Therefore, such recommendations were adopted to design the ratio of the alkaline solution in the analysed studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study [ 37 ] analysed the effect of NaOH concentration (6–14 M) on the mechanical properties of kaolin geopolymers. Compressive strength results showed that the optimum NaOH concentration is 8 M. Moreover, according to research results [ 3 , 4 , 11 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 37 , 38 , 39 , 40 , 42 , 43 ], the soluble glass to 8 M of NaOH solution ratio should be around 2.5 to give geopolymers high compressive strength [ 37 , 40 ]. Therefore, such recommendations were adopted to design the ratio of the alkaline solution in the analysed studies.…”
Section: Methodsmentioning
confidence: 99%
“…If the geopolymer is foamed in the production process, it might become lightweight and partly insulating [ 6 , 36 ]. On the other hand, in an almost pore-free form, the geopolymer may be used to protect walls against moisture and fungi formation [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the recovery process is regarded as unsuccessful for particles smaller than 8 mm [13]. The presence of metallic aluminum affects the mechanical behaviour of AABs, since it leads to a porosity increase due to the generation of hydrogen gas from the reaction between aluminum contained in IBA and the alkaline activators [36]. In contrast, the coarser fractions of IBAs are richer in glass (cullet) from containers and there is greater availability of SiO 2 for gelation reactions [13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Salas et al [7] scaled the introduction of large amounts of industrial inorganic into fired clay cycles up to industrial production without significantly altering the technical properties of products. Furthermore, Piccolo et al [8] developed AAM-exploiting biochar, a secondary raw material coming from pyrolysis/gasification processes, for the improvement of soil fertility and reduction of CO 2 emissions because of the carbon sink process. Because of the promising technical results obtained, the AAM can be used for insulating panels or lightweight materials for houses and gardens in terraces and balconies.…”
mentioning
confidence: 99%